Impact of Intensive Lifestyle Intervention on Preference-based Quality of Life in Type 2 Diabetes: Results from the Look AHEAD Trial - Zhang, Ping (Obesity (Silver Spring), 2016)
OBJECTIVE: To assess the effect of an intensive lifestyle intervention (ILI) compared with standard diabetes support and education (DSE) on preference-based health-related quality of life (HRQOL) in persons with overweight or obesity and type 2 diabetes. METHODS: Look AHEAD was a multisite, randomized trial of 5145 participants assigned to ILI or DSE. Four instruments were administered during the trial: Feeling Thermometer (FT), Health Utilities Index Mark 2 (HUI2), Health Utilities Index Mark 3 (HUI3), and Short Form 6D (SF-6D). Linear mixed effect models were used to estimate the mean difference in preference scores by treatment group over 9 years. RESULTS: The ILI had higher mean FT (0.019, 95% CI, 0.015 to 0.024, p<0.001) and SF-6D (0.011, 95% CI, 0.006 to 0.014, p<0.001) scores than the DSE. No significant group-differences were observed for the HUI2 (0.004, 95% CI, -0.003 to 0.010, p=0.23) and HUI3 (0.004, -0.004 to 0.012, p=0.36). In year one, the ILI had higher mean preference scores for all instruments. Thereafter, the increases remained significant only for FT and SF-6D and the effects also become smaller. CONCLUSIONS: ILI aimed at reducing bodyweight among persons with overweight or obesity and type 2 diabetes improves preference-based HRQOL in the short term, but its long-term effect is unclear.